Interferensi Leksikal Pada Vlog Kenta Manis Channel berjudul “Kenta Pamit, Semua Nangis Denger Surat dari Kenta” - Tresnasari, Ningrum; Muhammad Akbar, Faizal; Muhammad Rafif, Naufal; Jagadhita, Raditya (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 2 (2021)DO - 10.24843/JS.2021.v03.i02.p02, 2021)
Lexical interference is the case most often encountered in the speech community. This occurs when speakers (regardless of foreign or native speakers) experience vocabulary limitations or do not know the exact vocabulary equivalent in a particular language. The purpose of this study was to identify the forms of lexical interference contained in the kenta manis channel vlog entitled "Kenta Pamit, All Nangis Denger Surat from Kenta". The research method used is descriptive qualitative data collection methods observation method and the method of analysis used is the orthographic equivalent method. The data source used in this study came from the YouTube vlog of Kenta Manis channel. The total amount of lexical interference data in the study was 8 pieces of data. From the analysis that has been done, it can be concluded that lexical interference by kenta in his vlog is divided into two classifications, namely there are 7 lexical interference in English and 1 lexical interference in Chinese.